DEMAND FORECASTING FOR DC MACHINES WITH APPLICATION OF FORMALIZED GROWTH-CURVE-BASED MODELS - O.N. Dubinina (National Technical University "Kharkiv Polytechnic Institute", 2013)
Demand forecasting for DC machines produced by ELECTROMASHINA Public Corporation (Kharkov, Ukraine) is performed with application of formalized models based on growth curves. Types of DC machines which are most promising for rebuilding are ascertained.